Innovation cycles and productivity gain in the maritime transport (port innovation) - Low, Edmund Chee Kiat (2018)
Innovation is an essential driver of competiveness in today’s port industry. As business environment becomes uncertain and competitive, port operators need to integrate both technological and non-technological innovations in regards to organisation, people and services so as to succeed and survive. It is generally recognized that innovation enhances productivity as numerous empirical studies have established a positive relationship of innovation on productivity. However, limited studies have been done on analysing how these productivity growth can be translated into financial gains. Therefore, this paper aims to investigate the monetary benefits port operators can achieved from various innovations. The paper will evaluate some of the past port innovations that have been adopted since the introduction of containerisation. Following which, detailed analyses on current and future innovation will be conducted to determine the change in productivity. In order to examine the impact of different innovations on financial gains, cost models from various authors were employed in the calculations of financial savings. Primary research, in the form of face-to-face interview, is also conducted to obtain industrial insights on port innovation. At the end of this study, it can be concluded that most current and future port innovations have significant contribution on productivity; in terms of waiting time and container movements, and financial gains – although some of them are difficult to quantify due to insufficient information.